2000
DOI: 10.1128/jb.182.21.6161-6168.2000
|View full text |Cite
|
Sign up to set email alerts
|

A Sheep in Wolf's Clothing: Listeria innocua Strains with Teichoic Acid-Associated Surface Antigens and Genes Characteristic of Listeria monocytogenes Serogroup 4

Abstract: Listeria monocytogenes serotype 4b has been implicated in numerous food-borne epidemics and in a substantial fraction of sporadic listeriosis. A unique lineage of the nonpathogenic species Listeria innocua was found to express teichoic acid-associated surface antigens that were otherwise expressed only by L. monocytogenes of serotype 4b and the rare serotypes 4d and 4e. These L. innocua strains were also found to harbor sequences homologous to the gene gtcA, which has been shown to be essential for teichoic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 30 publications
1
36
0
Order By: Relevance
“…By these methods the species is divided into two genetic divisions which are correlated with the flagellar antigen groups division I, composed of strains of serotypes 1/2a and 1/2c, and division II, which is composed of strains of serotypes 1/2b and 4b. Both divisions are characterized by nonoverlapping allelic variants of different genetic markers, suggesting strong linkage disequilibrium and an apparent lack of gene exchange between them (15). This is consistent with the hypothesis that the genetic structure of L. monocytogenes populations is basically clonal (21).…”
supporting
confidence: 75%
“…By these methods the species is divided into two genetic divisions which are correlated with the flagellar antigen groups division I, composed of strains of serotypes 1/2a and 1/2c, and division II, which is composed of strains of serotypes 1/2b and 4b. Both divisions are characterized by nonoverlapping allelic variants of different genetic markers, suggesting strong linkage disequilibrium and an apparent lack of gene exchange between them (15). This is consistent with the hypothesis that the genetic structure of L. monocytogenes populations is basically clonal (21).…”
supporting
confidence: 75%
“…4). Evidence for horizontal transfer between L. monocytogenes serotype 4b and L. innocua has been described before (19). Alternatively, ORFs conserved in L. monocytogenes serotype 4b and L. innocua may represent ancestral sequences that have become eliminated from other L. monocytogenes lineages.…”
Section: Discussionmentioning
confidence: 99%
“…From there it could have been transferred to lineage I of L. innocua, as has been speculated for the gtcA locus recently identified in this lineage (9). The origin of the serotype-specific sequences may be elucidated by future identification of homologous sequences in other bacteria or bacteriophage.…”
Section: Discussionmentioning
confidence: 99%
“…Hybridizations using probe XL7-AB, which contains both gltA and gltB, showed that the genes were unique to L. monocytogenes serotype 4b-4d-4e and could not be detected in DNA from strains of other serotypes. The genes have also been detected in a unique lineage (lineage I) of L. innocua (9). EcoRI restriction fragment length polymorphisms using XL7-AB as the probe could differentiate between L. monocytogenes serotype 4b-4d-4e and L. innocua lineage I (Table 1).…”
Section: Vol 183 2001 Novel Serotype-specific Gene Cassette Of L Mmentioning
confidence: 96%